The Firms behind the Regions: Analysis of Regional Innovation Performance in Portugal by External Logistic Biplots - Teresa de Noronha; Purificación Vicente Galindo; Peter Nijkamp; Eric de Noronha Vaz (Tinbergen Institute, 2013)
The strategic choices regarding innovation and R&D policy in Portugal have, over the last two decades, produced various positive benefits, in which particularly the regions of Lisbon and Algarve have taken the lead. These are the only parts of the country that converge towards the European average growth rate. The other Lisbon and Algarve have taken the lead, and are the only ones in the country to converge towards the European average growth rate. Other Portuguese regions – despite significant national growth rates in the 1990s and a successful attempt to cope with the EMU – are lagging behind the EU average with respect to gross production, investment and employment generation. Meanwhile, one of the greatest public policy efforts was to diffuse much of the European funds across the entrepreneurial sector. This paper aims to evaluate the firms' contribution to national and regional growth, their obstacles and impacts, and to explain the present performance of Portuguese firms located throughout the country, and to explore those innovation determinants that have a region-specific connotation. In our paper, innovation is used as a major contributor to the policy evaluation process referred to above. To provide a thorough investigation, our analysis defines, on a regional basis, a set of firms' behavioural patterns regarding innovation. In our modelling, we employ a new methodology, viz. the External Logistic Biplot method, which is applied to an extensive sample of innovative institutions in Portugal. Variables such as `Promoting knowledge', `Management skills', `Promoting R&D', `Knowledge transfer', `Promoting partnership & cooperation', and `Orientation of public measures' have been identified as crucial determinants in earlier studies and are now used to describe regional institutional profiles.
Keywords: O50; O3; 330; Regional Asymmetries; Innovation; Firms' Performance; Regional Innovation Systems; Principal Coordinates Analysis; External Logistic Biplot; Voronoi Diagram; Dissimilarity Matrix